Situational Language Teaching in Ubiquitous Learning Environments - Angus F.M. Huang; Stephen J.H. Yang; Gwo-Jen Hwang (Knowledge Management & E-Learning: An International Journal, 2010)
Situational language teaching (SLT) is an effective instruction paradigm for English teaching in terms of providing vocabularies and sentence patterns with their frequent situations through learning materials. With the growth of educational technology, we need powerful and suitable techniques to embody SLT’s features in ubiquitous learning (u-learning) and thus to benefit teachers and learners. Although researchers have proposed several innovative types of u-learning scenarios, the improved SLT paradigm in u-learning environment has been rarely investigated. This study indicated a framework of ubiquitous learning school to promote the concept of u-learning and employ SLT pedagogy in u-learning environment; it is called U-SLT. In order to support its innovation and provide situational learning services on demand, situational mashups was suggested to identify learners’ situation and learning requirement by means of integrating situation awareness with service mashups. The comparison between two u-learning modes, learning with situational mashups and learning without situation awareness support, were discussed. Experimental results showed that the students with the situational mashups support had a better learning performance and improved behaviours. Therefore, situational mashups was perceived to be a useful and desirable system for supporting U-SLT as well as the fundamental issue of a ubiquitous learning school.